Pengaruh Persepsi Mahasiswa tentang Profesi Guru terhadap Minat menjadi Guru pada Mahasiswa Pendidikan Teknik Mesin Universitas Negeri Padang - Muhamad Fadel; Jasman Jasman; Eko Indrawan; Budi Syahri (Lembaga Yasin AlSys, 2026)
Although the teaching profession has a strategic role in ensuring the quality of vocational education, not all students in education study programs show a strong interest in pursuing a career as teachers. This study aims to analyze the effect of students’ perceptions of the teaching profession on interest in becoming teachers among students of the Mechanical Engineering Education Study Program at Universitas Negeri Padang. This study used a quantitative approach with an associative ex post facto design. The population as well as the research sample consisted of 72 students from the 2022 cohort, determined through a total sampling technique. Data were collected using a four-point Likert-scale questionnaire distributed through Google Forms. The research instrument consisted of 35 valid items with a Cronbach’s Alpha reliability coefficient of 0.949. Data were analyzed using descriptive statistics, normality testing, linearity testing, and simple linear regression with the assistance of SPSS. The results showed that students’ perceptions of the teaching profession were in the good category, with the largest percentage of 36%, while interest in becoming teachers was also in the good category, with the largest percentage of 44%. The regression analysis produced the equation Y = 10.348 + 0.448X, while the t-test obtained a value of 4.718 with a significance of 0.000 < 0.05. These findings indicate that students’ perceptions of the teaching profession have a positive and significant effect on interest in becoming teachers. The conclusion of this study affirms that the more positive students’ perceptions of the teaching profession, the higher their interest in choosing a teaching career. The implications of this study emphasize the importance of strengthening understanding, experience, and a positive image of the teaching profession in vocational education programs so that students’ interest in becoming teachers can develop more optimally.